Impacto de inseticidas sintéticos (piriproxifen e sulfoxaflor) na reprodução do inseto não alvo Ceraeochrysa claveri (Navás, 1911) (Neuroptera: Chrysopidae): estudo molecular e morfológico - Tomacheski, Jefferson Fogaça [UNESP] (UNESP, 2025)
Insect pest management often involves optimizing and combining the use of selective insecticides with biological control methods involving natural enemies. Insecticides like pyriproxyfen and sulfoxaflor have various effects on pests (target insects) and non-target insects such as natural predators, with the goal of minimizing toxicity to beneficial arthropods. Tolerance to insecticides in non-target insects is a desirable trait because conserving and maintaining beneficial insects can help control pest populations and prevent the resurgence of secondary pests. Therefore, understanding the sublethal effects of insecticides on both pests and their natural enemies, as well as the potential for natural enemies to tolerate these chemicals, can enhance integrated pest management (IPM) strategies and promote more sustainable agriculture. This study aimed to analyze the late sublethal effects of pyriproxyfen on the testes of adult Ceraeochrysa claveri (Navás, 1911) (Neuroptera: Chrysopidae) exposed during the larval stage, and to evaluate the cellular responses of the ovaries and testes of adults exposed to sulfoxaflor during the same stage. We analyzed RNA-seq data from males exposed to pyriproxyfen during the larval stage (Garcia, 2021) to identify differentially expressed genes (DEGs). Using this data, we assembled the testis transcriptome de novo, annotated genes based on ORF homology, and created a counting matrix to identify DEGs. Four genes were selected for validation via RT-qPCR: BPHL, Large2, MLX, and Talin-1. First-instar C. claveri larvae were fed Diatraea saccharalis (Lepidoptera: Crambidae) eggs containing different concentrations of sulfoxaflor for 10 days. We then analyzed their life cycle and survival after they emerged as adults. Additionally, tests and ovaries from 10-day-old adults were collected for histological analysis using light and transmission electron microscopy. No significant differences in developmental time or survival rates were observed between the sulfoxaflor-treated insects and the control group. Although spacing between cells was noted in the reproductive organs, no visible damage to spermatogenesis or oogenesis was detected. Overall, this work showed that pyriproxyfen and sulfoxaflor can cause some damage to the reproductive organs of C. claveri and induce changes in gene expression (notably with pyriproxyfen). However, these insecticides did not disrupt the processes of spermatogenesis and oogenesis, suggesting a possible tolerance and compatibility with IPM strategies aimed at sustainable pest control.

O manejo de pragas de insetos geralmente depende da otimização e combinação do uso de inseticidas seletivos e controle biológico por inimigos naturais. Inseticidas, como piriproxifen e sulfoxaflor, apresentam vários efeitos sobre pragas (insetos-alvo) e predadores naturais (insetos não-alvo), buscando exercer efeitos de baixa toxicidade sobre artrópodes benéficos. A tolerância a inseticidas é uma característica desejável para insetos não-alvo, uma vez que a conservação e manutenção de insetos benéficos podem controlar o crescimento populacional de pragas e/ou o ressurgimento de pragas secundárias. Assim, o conhecimento dos efeitos subletais de inseticidas sobre pragas de insetos e seus inimigos naturais, bem como a tolerância potencial de inimigos naturais a inseticidas, pode melhorar as estratégias de manejo integrado de pragas, contribuindo para uma agricultura mais sustentável. Este estudo teve como objetivo analisar o efeito subletal de dois inseticidas com modos de ação diferentes: verificar uma possível alteração sobre a expressão gênica dos testículos de adultos de Ceraeochrysa claveri (Navás, 1911) (Neuroptera: Chrysopidae) expostos ao inseticida piriproxifen durante a fase larval, e avaliar a resposta celular dos ovários e testículos de adultos de C. claveri expostos ao inseticida sulfoxaflor, também durante a fase larval. Dados oriundos de RNAseq de machos expostos à duas doses do inseticida piriproxifen (50 mg i.a. L−1e 100 mg i.a. L−1) durante a fase larval foram analisados para identificar genes diferencialmente expressos relacionados. Por meio de dados de RNA-seq, as leituras foram montadas de novo para construir o transcriptoma do testículo, os genes foram anotados por homologia de ORFs e uma matriz de contagem foi construída para obter os genes diferencialmente expressos (GDEs). Quatro DEGs foram selecionados para serem validados por RT-qPCR: BPHL, Large2, MLX e Talin-1. Larvas de primeiro ínstar de C. claveri foram alimentadas com ovos de Diatraea saccharalis (Lepidoptera: Crambidae) contendo diferentes concentrações de sulfoxaflor (15,02 mg i.a. L-1, 45,05 mg i.a. L-1 e 75,10 mg i.a. L-1) por 10 dias. O ciclo de vida e a sobrevivência foram analisados após os insetos emergirem para adultos. Testículos e ovários de adultos de 10 dias de idade de C. claveri foram coletados para análises histológicas sob microscopia óptica e eletrônica de transmissão. Nenhuma alteração nos dias de desenvolvimento e sobrevivência foi encontrada quando os insetos tratados com sulfoxaflor foram comparados ao grupo controle. Os testículos e ovários exibiram espaçamentos entre as células, sem danos visíveis às células da linhagem espermatogênica e oogênica. Este trabalho demonstrou que o inseticida piriproxifen modificou a expressão gênica do testículo de C. claveri, e que o inseticida sulfoxaflor alterou a morfologia dos órgãos reprodutivos deste inseto, porém sem danos às células da linhagem espermatogênica e oogênica, indicando uma possível tolerância e compatibilidade desses inseticidas associados ao manejo integrado de pragas (MIP).
Impact of synthetic insecticides (pyriproxyfen and sulfoxaflor) on the reproduction of the non-target insect Ceraeochrysa claveri (Navás, 1911) (Neuroptera: Chrysopidae): molecular and morphological study
Keywords: Biologia molecular; Inseticidas; Insetos controle